2019
DOI: 10.1210/jc.2019-00734
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Phenotypes of Type 1 Diabetes in Youth Based on Weight and Glycemia and Their Association With Complications

Abstract: Context Subclinical and clinical complications emerge early in type 1 diabetes (T1D) and may be associated with obesity and hyperglycemia. Objective Test how longitudinal “weight-glycemia” phenotypes increase susceptibility to different patterns of early/subclinical complications among youth with T1D. Design SEARCH for Diabetes in Youth observational study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…This is an unsupervised nonparametric technique that simultaneously partitions user trajectories from both the social and therapy dimensions into distinct cluster groups. This technique uses a hill-climbing expectation-maximization algorithm, alternating through various initialization methods until convergence is reached [45,47].…”
Section: Identifying User Profilesmentioning
confidence: 99%
“…This is an unsupervised nonparametric technique that simultaneously partitions user trajectories from both the social and therapy dimensions into distinct cluster groups. This technique uses a hill-climbing expectation-maximization algorithm, alternating through various initialization methods until convergence is reached [45,47].…”
Section: Identifying User Profilesmentioning
confidence: 99%
“…Higher residual beta cell function confers lower risk of microalbuminuria and retinopathy [12]. Recently, the SEARCH for Diabetes in Youth study showed different patterns of subclinical macrovascular complications according to phenotypes of different combinations of weight and glucose levels in blood [13]. A number of studies have shown influence on complications by candidate genes such as the VEGF gene for retinopathy, the ADIPOQ gene for coronary artery disease and the ELMO1 gene for nephropathy, although replication remains controversial (reviewed in [14]).…”
Section: Heterogeneity Of Diabetes Within Types and Clinical Consequementioning
confidence: 99%
“…Indeed, overweight and obese youth with type 1 diabetes are more likely to have coexisting hypertension, abnormal lipids, and elevated alanine aminotransferase compared to healthy weight peers ( 110 , 111 ). In the SEARCH registry, youth with obesity and persistently elevated hemoglobin A1c over time had the highest risk for adverse cardiovascular markers and microvascular complications compared to those with either elevated hemoglobin A1c and normal weight or obesity with fairly-well controlled A1c ( 112 ). In clamp studies, our group found that obese youth with type 1 diabetes were more insulin resistant compared to non-obese peers with type 1 diabetes.…”
Section: Added Risk For Micro- and Macrovascular Complicationsmentioning
confidence: 99%